Semi-solid lithium ion battery and preparation method thereof

By using a double-layer coating process to build a positive electrode-supported solid electrolyte film frame in a semi-solid lithium-ion battery, the problem of poor contact between the solid electrolyte film and the positive electrode material is solved, the ionic conductivity and cyclic stability of the battery are improved, and the The overall performance and safety of the battery.

CN119181837APending Publication Date: 2024-12-24HUADING GUOLIAN SICHUAN POWER BATTERY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411272512.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing semi-solid lithium-ion batteries have problems such as poor interface contact between the solid electrolyte membrane and the positive electrode material, low ion conductivity, large interface impedance, insufficient mechanical properties and stability, which leads to the difficulty of the electrolyte sufficiently under high pressure and poor circulation performance of the battery. .

Method used

The positive electrode supports solid electrolyte film frame is constructed by a double-layer coating process. By mixing slurries of active substances, conductive agents, binders and nanofillers, a solid electrolyte layer with rich ions is formed to block the direct contact between the positive electrode material and the liquid electrolyte. Contact, reduce interface impedance and improve the ion conduction performance of the battery.

Benefits of technology

It improves the energy density, rate performance and cycle life of the battery, enhances the safety and stability of the battery, reduces the use of liquid electrolyte, reduces the risk of leakage and combustion, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181837A_ABST
    Figure CN119181837A_ABST
Patent Text Reader

Abstract

The invention discloses a semi-solid lithium ion battery and a preparation method thereof, and belongs to the technical field of lithium ion batteries. The semi-solid lithium ion battery comprises a positive plate, a negative plate, a diaphragm and an electrolyte, the positive plate and the negative plate are separated by the diaphragm, a battery cell is formed by lamination in a mode of wrapping a positive electrode by a negative electrode, the battery cell is packaged into a battery shell, electrolyte is injected, and the semi-solid lithium ion battery is obtained through processes of pre-charging, degassing and capacity grading. According to the invention, a positive electrode support type solid electrolyte film frame is constructed through double-layer coating of the positive plate, so that the ionic conductivity of the battery is improved, the interface impedance is reduced, the energy density and rate capability of the battery are improved, the cycle life of the battery is prolonged, and the safety and stability of the battery are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a semi-solid lithium ion battery and a preparation method thereof. Background Art

[0002] As a high energy density and long life electrochemical energy storage device, lithium-ion batteries are widely used in portable electronic devices, electric vehicles and energy storage systems. Existing lithium-ion batteries are mainly divided into three types: liquid batteries, all-solid-state batteries and semi-solid-state batteries. Liquid lithium-ion batteries still dominate the market due to their high conductivity and mature production process. However, the organic electrolyte in liquid batteries is flammable and has leakage and safety hazards. All-solid-state lithium-ion batteries have the potential for high safety and high energy density due to the use of solid electrolytes, but their solid electrolytes have low ion conductivity, large interface impedance, complex preparation process and high cost. Although semi-solid lithium-ion batteries have solved the safety issues of liquid batteries to a certain extent, there are still some technical challenges. For example, the interface contact between the solid electrolyte membrane and the positive electrode material is poor, resulting in reduced ion conductivity and increased interface impedance. In addition, the mechanical properties and stability of the solid electrolyte membrane also need to be improved.

[0003] A Chinese patent with publication number CN113745454A discloses a positive electrode sheet, its preparation method and application in a semi-solid battery. The patent introduces an oxide solid electrolyte into the positive electrode through slurry. The polymer obtained by in-situ polymerization can effectively improve the contact between the oxide solid electrolyte and the material in the positive electrode sheet, reduce the impedance of the positive electrode sheet, and improve the electrochemical performance of the positive electrode sheet. However, in the context of the pursuit of high compaction of the positive electrode, it is difficult for the electrolyte to fully infiltrate or fill the gap in the electrode sheet, which leads to uneven in-situ polymerization and uneven lithium deposition during battery charging and discharging. In addition, the gel polymer solid electrolyte formed by in-situ polymerization has low ion conductivity itself, accompanied by the continuous consumption of electrolyte during the cycle, resulting in poor battery cell cycle performance.

[0004] A Chinese patent with publication number CN114335716A discloses an in-situ polymerization solid-state battery with a multilayer structure electrolyte and a preparation method thereof. The patent performs in-situ polymerization by mixing reactive monomers into the positive and negative electrodes and adding reaction aids such as a crosslinking agent into the electrolyte. However, if it is necessary to simultaneously satisfy the reaction of the crosslinking agent with the positive and negative electrodes, the selection of materials is very strict, and the system that can be selected is very limited, which greatly limits the original intention of the positive electrode being resistant to oxidation, the negative electrode being resistant to reduction, and both the positive and negative electrodes being able to exert their effects. If two initiators or reaction systems are selected, the two initiators or reaction systems will produce a competitive relationship and mutual influence, resulting in incomplete reaction, and the polymerization reaction needs to be carried out quickly after the electrolyte is injected, otherwise the monomers of the positive and negative electrodes will penetrate each other as the electrolyte infiltrates, and ultimately weaken the effect of the positive and negative electrode stratification, thereby affecting the battery's rate performance, cycle performance, etc. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a semi-solid lithium ion battery and a preparation method thereof. A semi-solid lithium ion battery with a positive electrode coated with a solid electrolyte membrane prepared by the preparation method of the present invention improves the ion conductivity of the battery, reduces the interface impedance, improves the energy density, rate performance and cycle life of the battery, and enhances the safety and stability of the battery.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0007] The present invention provides a semi-solid lithium ion battery, comprising: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the separator separates the positive electrode sheet from the negative electrode sheet, a negative electrode is wrapped around the positive electrode and the sheets are stacked to form a battery core, the battery core is packaged into a battery shell, an electrolyte is injected, and the semi-solid lithium ion battery is obtained after pre-charging, degassing and capacity separation processes.

[0008] The present invention provides a method for preparing a semi-solid lithium-ion battery, which specifically comprises the following steps:

[0009] (1) mixing and homogenizing the active material, the conductive agent, the binder and the dispersant to obtain a first slurry;

[0010] (2) mixing and homogenizing the solid electrolyte, the binder, the ionic liquid and the nanofiller to obtain a second slurry;

[0011] (3) coating the first slurry on the current collector through a double-layer coating process, coating the second slurry on the first slurry, and obtaining a positive electrode sheet through rolling, slitting, and die-cutting processes;

[0012] (4) Mix graphite, silicon-based anode, conductive agent and binder, and perform homogenization treatment to obtain anode slurry. After coating, rolling, slitting and die-cutting processes, obtain anode sheets;

[0013] (5) Assemble the positive electrode sheet, negative electrode sheet and separator into a core package by stacking, and obtain a dry battery cell through welding, inserting into an aluminum-plastic film shell and heat-sealing processes;

[0014] (6) Inject electrolyte into the dry battery cell, and obtain a semi-solid state lithium-ion battery through processes of pre-charging, degassing and grading;

[0015] As a preferred embodiment, in step (1), the active material is selected from one or more of ternary material LiNi x Co y M 1-x-y O2, lithium iron phosphate, lithium manganese iron phosphate, etc. In the ternary material LiNi x Co y M 1-x-y O2, M is at least one of Mn and Al, 0.4 ≤ x < 1, 0 < y < 0.2; the conductive agent is selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, Super-P, etc.; the binder is selected from one or two of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; the dispersant is selected from one or two of tripropyl phosphate, dibutyl phosphate, polyether-modified polysiloxane copolymer, etc.

[0016] As a preferred embodiment, in step (1), the mass ratio of the active material, conductive agent, binder and dispersant is (95-99.25):(0.2-5):(0.5-2):(0.05-0.5).

[0017] As a preferred embodiment, in step (2), the solid electrolyte is selected from one or more of lithium lanthanum zirconium titanium oxide, lithium aluminum titanium phosphate, lithium zirconium silicon phosphorus oxide, etc.; the binder is selected from one or two of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; the ionic liquid is selected from one or more of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium dicyanamide, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-ethyl-3-methylimidazolium dicyanomethane, 1-butyl-3-methylimidazolium dicyanamide, 1-butyl-3-methylimidazolium dicyanamide, etc.; the nano filler is selected from one or more of titanium dioxide, silicon dioxide, graphene, Maxi, etc.

[0018] As a preferred embodiment, in step (2), the mass ratio of the solid electrolyte, binder, ionic liquid and nano filler is (20-99):(0.5-60):(0.4-20):(0-5).

[0019] As a preferred embodiment, in step (4), the silicon-based negative electrode is selected from one or more of silicon oxide, silicon carbon, and silicon nanowires; the conductive agent is selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and Super-P; the binder is selected from one or more of polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose, and styrene-butadiene rubber.

[0020] As a preferred embodiment, in step (4), the mass ratio of the graphite, the silicon-based negative electrode, the conductive agent and the binder is (1-96): (1-96): (0.1-5): (1-5).

[0021] As a preferred embodiment, in step (5), the diaphragm is selected from a ceramic single-sided / double-sided coated diaphragm, a solid electrolyte single-sided / double-sided coated diaphragm, and a single-sided / double-sided glue-coated diaphragm.

[0022] As a preferred embodiment, in step (3), the coating thickness of the second slurry is 2-20 μm.

[0023] As a preferred embodiment, in step (6), the electrolyte accounts for 2-15% of the total weight of the dry battery cell.

[0024] The beneficial effects of the present invention are:

[0025] 1. The present invention is different from the traditional semi-solid state battery. It does not need to adopt the in-situ curing strategy, and can avoid the problems of in-situ curing such as difficulty in achieving uniform polymerization, material failure caused by free radicals attacking the active materials of the battery cell after high-temperature curing, increased internal resistance and rapid attenuation.

[0026] 2. The present invention constructs a positive electrode supporting solid electrolyte film frame by double-layer coating of the positive electrode sheet, which can effectively block the direct contact between the positive electrode material and the liquid electrolyte, prevent the occurrence of side reactions, and thus reduce the loss of battery capacity.

[0027] 3. The positive electrode supporting solid electrolyte film frame constructed by the present invention can maintain stability under high voltage, improve the voltage window of the material, and thus improve the capacity and energy density of the entire battery.

[0028] 4. The positive electrode supporting solid electrolyte film frame constructed by the present invention can improve the ion conductivity of the battery, so that the battery can maintain good electrochemical performance even at low temperatures.

[0029] 5. The positive electrode supporting solid electrolyte film frame constructed by the present invention can reduce the volume change of the battery during the charging and discharging process, thereby improving the cycle stability and life of the battery.

[0030] 6. A method for preparing a semi-solid lithium-ion battery of the present invention adopts a double-layer coating process for the positive electrode-supported solid electrolyte film frame process. The solid electrolyte coating is easy to form, easy to operate, and convenient for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the solid electrolyte coating in Example 1. DETAILED DESCRIPTION

[0032] The invention provides a semi-solid lithium ion battery, which mainly comprises: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The positive electrode sheet and the negative electrode sheet are separated by the separator, and a battery core is formed by stacking the sheets in a manner of encapsulating the positive electrode with the negative electrode, and the battery core is packaged into a battery shell and injected with an electrolyte. After precharging, degassing and capacity separation processes, a semi-solid lithium ion battery is obtained.

[0033] The present invention constructs a positive electrode support type solid electrolyte film framework through a double-layer coating process, with active materials such as ternary materials as the lower layer, and materials such as oxide solid electrolytes and nanofillers as the upper layer, and the solid electrolyte film framework of the upper layer is mainly composed of ion-conducting solid electrolytes, lithium salts, electron-conducting nanofillers, binders and ionic liquids. Composite solid electrolyte slurry is directly coated on the positive electrode coating through a double-layer coating process, and the holes inside the positive electrode coating are filled with solid electrolyte slurry, and the two are well and closely contacted so that the wettability between the solid electrolyte and the positive electrode is good, thereby reducing the interface impedance, facilitating the conduction of ions across the interface, and improving the rate performance and cycle life of the battery core. In addition, the safety of the battery can also be improved, the usage of liquid electrolyte can be reduced, the risk of leakage and combustion can be reduced, and the overall performance and application prospects of the battery can be further enhanced.

[0034] The present invention provides a method for preparing a semi-solid lithium-ion battery, which specifically comprises the following steps:

[0035] (1) The active material, the conductive agent, the binder and the dispersant are mixed and homogenized in a mass ratio of (95-99.25):(0.2-5):(0.5-2):(0.05-0.5) to obtain a first slurry.

[0036] Preferably, in step (1), the active material is selected from the ternary material LiNi x Co y M 1-x-y One or more of O2, lithium iron phosphate, and lithium iron manganese phosphate, but not limited thereto.

[0037] Among them, the ternary material LiNi x Co y M 1-x-yIn O2, M is at least one of Mn and Al, 0.4≤x<1, 0 <y<0.2。

[0038] Preferably, in step (1), the conductive agent is selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and Super-P, but is not limited thereto.

[0039] Preferably, in step (1), the binder is selected from one or both of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), but is not limited thereto.

[0040] Preferably, in step (1), the dispersant is selected from one or two of tripropyl phosphate (TPP), dibutyl phosphate (TBP), and polyether-modified polysiloxane copolymer, but is not limited thereto.

[0041] (2) The solid electrolyte, the binder, the ionic liquid and the nanofiller are mixed and homogenized in a mass ratio of (20-99): (0.5-60): (0.4-20): (0-5) to obtain a second slurry.

[0042] Preferably, in step (2), the solid electrolyte is selected from one or more of lithium lanthanum zirconium titanate, lithium aluminum titanium phosphate (LATP), and lithium zirconium silicon phosphorus oxide, but is not limited thereto.

[0043] Preferably, in step (2), the binder is selected from one or both of polyvinylidene fluoride (PVDF) and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), but is not limited thereto.

[0044] Preferably, in step (2), the ionic liquid is selected from one or more of 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium dinitrile amine salt, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-ethyl-3-methylimidazolium dicyanomethylene salt, 1-butyl-3-methylimidazolium dicyanamide salt, and 1-butyl-3-methylimidazolium dicyanamide salt. But not limited thereto.

[0045] Preferably, in step (2), the nanofiller is selected from one or more of titanium dioxide, silicon dioxide, graphene, and Maxim, but is not limited thereto.

[0046] (3) The first slurry is coated on the current collector through a double-layer coating process, and the second slurry is coated on the first slurry, and the positive electrode sheet is obtained through rolling, slitting, and die-cutting processes.

[0047] Preferably, in step (3), the coating thickness of the second slurry is 2-20 μm.

[0048] (4) Graphite, silicon-based negative electrode, conductive agent and binder are mixed and homogenized in a mass ratio of (1-96): (1-96): (0.1-5): (1-5) to obtain negative electrode slurry, and negative electrode sheets are obtained through coating, rolling, slitting and die-cutting processes.

[0049] Preferably, in step (4), the silicon-based negative electrode is selected from one or more of silicon-oxygen, silicon-carbon, and silicon nanowires, but is not limited thereto.

[0050] Preferably, in step (4), the conductive agent is selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and Super-P, but is not limited thereto.

[0051] Preferably, in step (4), the binder is selected from one or more of polyacrylic acid (PAA), polyacrylonitrile (PAN), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), but is not limited thereto.

[0052] (5) The positive electrode sheet, the negative electrode sheet and the separator are assembled into a core package by stacking, and a dry battery cell is obtained by welding, shelling with aluminum-plastic film and heat sealing.

[0053] Preferably, in step (5), the diaphragm is selected from one of a ceramic single-sided / double-sided coated diaphragm, a solid electrolyte single-sided / double-sided coated diaphragm, and a single-sided / double-sided glue coated diaphragm, but is not limited thereto.

[0054] (6) The electrolyte is injected into the dry battery cell, and a semi-solid lithium-ion battery is obtained after pre-charging, degassing, and capacity separation processes.

[0055] Preferably, in step (6), the electrolyte accounts for 2-15% of the total weight of the dry battery cell.

[0056] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0057] Example 1 Preparation of a semi-solid lithium ion battery

[0058] (1) Ni90 ternary material (single crystal: polycrystalline = 2:8), multi-walled carbon nanotube conductive liquid, Super-P, and PVDF are mixed and homogenized in a mass ratio of 95:1.5:1.5:2 to obtain a first slurry;

[0059] (2) mixing and homogenizing LATP, PVDF-HFP, 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide and silica in a mass ratio of 45:40:10:5 to obtain a second slurry;

[0060] (3) coating the first slurry on the current collector through a double-layer coating process, coating the second slurry on the first slurry, and controlling the coating thickness of the second slurry to be 5 μm; further obtaining the positive electrode sheet through rolling, slitting and die-cutting processes, and the solid electrolyte coating such as Figure 1 As shown;

[0061] (4) mixing and homogenizing graphite, silicon oxide, multi-walled carbon nanotubes, Super-P, and PAA at a mass ratio of 73:20:3:2:2, and further performing coating, rolling, slitting, and die-cutting processes to obtain a negative electrode sheet;

[0062] (5) Assembling the positive electrode sheet, the negative electrode sheet and the solid electrolyte single / double-sided coated separator into a core package by laminating, and further obtaining a dry battery cell by welding, aluminum-plastic film shelling, heat sealing and other processes;

[0063] (6) injecting electrolyte into the dry cell, wherein the electrolyte accounts for 10% of the total weight of the dry cell, soaking in an environment of 25° C. for 48 hours, and then soaking in an environment of 45° C. for 24 hours;

[0064] (7) Pre-charging, degassing, and capacity separation of the above-mentioned battery cell to obtain a semi-solid lithium-ion battery.

[0065] (8) The prepared semi-solid lithium-ion battery was subjected to capacity, cycle, electrical performance tests, and safety tests such as heating and acupuncture. The test results are shown in Table 1.

[0066] Example 2 Preparation of a semi-solid lithium ion battery

[0067] (1) Ni90 ternary material (single crystal: polycrystalline = 2:8), lithium manganese iron phosphate, multi-walled carbon nanotube conductive liquid, Super-P, PVDF, and tripropyl phosphate are mixed and homogenized in a mass ratio of 85:10:1.5:1.5:2:0.2 to obtain a first slurry;

[0068] (2) mixing and homogenizing LATP, PVDF-HFP, 1-cyanoethyl-2-ethyl-4-methylimidazole and silicon dioxide in a mass ratio of 75:10:10:5 to obtain a second slurry;

[0069] (3) coating the first slurry on the current collector through a double-layer coating process, coating the second slurry on the first slurry, and controlling the coating thickness of the second slurry to be 10 μm; further obtaining the positive electrode sheet through rolling, slitting and die-cutting processes;

[0070] (4) mixing and homogenizing graphite, silicon oxide, multi-walled carbon nanotubes, Super-P, and PAA at a mass ratio of 73:20:3:2:2, and further performing coating, rolling, slitting, and die-cutting processes to obtain a negative electrode sheet;

[0071] (5) Assembling the positive electrode sheet, the negative electrode sheet and the solid electrolyte single / double-sided coated separator into a core package by laminating, and further obtaining a dry battery cell by welding, aluminum-plastic film shelling, heat sealing and other processes;

[0072] (6) injecting electrolyte into the dry cell, wherein the electrolyte accounts for 10% of the total weight of the dry cell, soaking in an environment of 25° C. for 48 hours, and then soaking in an environment of 45° C. for 24 hours;

[0073] (7) Pre-charging, degassing, and capacity separation of the above-mentioned battery cell to obtain a semi-solid lithium-ion battery.

[0074] (8) The prepared semi-solid lithium-ion battery was subjected to capacity, cycle, electrical performance tests, and safety tests such as heating and acupuncture. The test results are shown in Table 1.

[0075] Example 3 Preparation of a semi-solid lithium ion battery

[0076] (1) mixing and homogenizing lithium iron phosphate, Super-P, PVDF, and tripropyl phosphate in a mass ratio of 96.8:1:2:0.2 to obtain a first slurry;

[0077] (2) mixing and homogenizing LATP, PVDF-HFP, 1-butyl-3-methylimidazolium dicyanamide and Maxi in a mass ratio of 75:7:15:3 to obtain a second slurry;

[0078] (3) coating the first slurry on the current collector through a double-layer coating process, coating the second slurry on the first slurry, and controlling the coating thickness of the second slurry to be 6 μm; further obtaining the positive electrode sheet through processes such as rolling, slitting and die cutting;

[0079] (4) mixing and homogenizing graphite, silicon oxide, multi-walled carbon nanotubes, Super-P, and PAA at a mass ratio of 92:5:0.5:1:1.5, and further performing coating, rolling, slitting, and die-cutting processes to obtain a negative electrode sheet;

[0080] (5) Assembling the positive electrode sheet, the negative electrode sheet and the solid electrolyte single / double-sided coated separator into a core package by laminating, and further obtaining a dry battery cell by welding, aluminum-plastic film shelling, heat sealing and other processes;

[0081] (6) injecting electrolyte into the dry cell, wherein the electrolyte accounts for 10% of the total weight of the dry cell, soaking in an environment of 25° C. for 48 hours, and then soaking in an environment of 45° C. for 24 hours;

[0082] (7) Pre-charging, degassing, and capacity separation of the above-mentioned battery cell to obtain a semi-solid lithium-ion battery.

[0083] (8) The prepared semi-solid lithium-ion battery was subjected to capacity, cycle, electrical performance tests, and safety tests such as heating and acupuncture. The test results are shown in Table 1.

[0084] Example 4 Preparation of a semi-solid lithium ion battery

[0085] (1) mixing and homogenizing Ni811 ternary material, multi-walled carbon nanotube conductive liquid, Super-P, PVDF, and polyether-modified polysiloxane copolymer at a mass ratio of 96.5:1.5:1:1:0.2 to obtain a first slurry;

[0086] (2) mixing and homogenizing LATP, PVDF, 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide and titanium dioxide in a mass ratio of 75:3:12:5 to obtain a second slurry;

[0087] (3) coating the first slurry on the current collector through a double-layer coating process, coating the second slurry on the first slurry, and controlling the coating thickness of the second slurry to be 12 μm; further obtaining the positive electrode sheet through processes such as rolling, slitting and die cutting;

[0088] (4) mixing and homogenizing graphite, silicon oxide, multi-walled carbon nanotubes, Super-P, and PAA in a mass ratio of 75:18:2.5:2.5:2, and further performing coating, rolling, slitting, and die-cutting processes to obtain a negative electrode sheet;

[0089] (5) Assembling the positive electrode sheet, the negative electrode sheet and the solid electrolyte single / double-sided coated separator into a core package by laminating, and further obtaining a dry battery cell by welding, aluminum-plastic film shelling, heat sealing and other processes;

[0090] (6) injecting electrolyte into the dry cell, wherein the electrolyte accounts for 5% of the total weight of the dry cell, soaking in an environment of 25° C. for 48 hours, and then soaking in an environment of 45° C. for 24 hours;

[0091] (7) Pre-charging, degassing, and capacity separation of the above-mentioned battery cell to obtain a semi-solid lithium-ion battery.

[0092] (8) The prepared semi-solid lithium-ion battery was subjected to capacity, cycle, electrical performance tests, and safety tests such as heating and acupuncture. The test results are shown in Table 1.

[0093] Comparative Example 1 Preparation of a Semi-solid Lithium Ion Battery

[0094] (1) Ni90 ternary material (single crystal: polycrystalline = 2:8), multi-walled carbon nanotube conductive liquid, Super-P, PVDF, and polyether-modified polysiloxane copolymer are mixed and homogenized in a mass ratio of 95:1.5:1.5:2:0.2, and then a positive electrode sheet is obtained through processes such as coating, rolling, slitting, and die-cutting;

[0095] (2) mixing and homogenizing graphite, silicon oxide, multi-walled carbon nanotubes, Super-P, and PAA in a mass ratio of 73:20:3:2:2, and further obtaining a negative electrode sheet through coating, rolling, slitting, and die-cutting processes;

[0096] (3) Assembling the positive electrode sheet, the negative electrode sheet and the solid electrolyte single / double-sided coated separator into a core package by laminating, and further obtaining a dry battery cell by welding, aluminum-plastic film shelling, heat sealing and other processes;

[0097] (4) injecting electrolyte into the dry cell, wherein the electrolyte accounts for 10% of the total weight of the dry cell, soaking in an environment of 25° C. for 48 hours, and then soaking in an environment of 45° C. for 24 hours;

[0098] (5) Pre-charging, degassing, and capacity separation of the above-mentioned battery cell to obtain a semi-solid lithium-ion battery.

[0099] (6) The prepared semi-solid lithium-ion battery was subjected to capacity, cycle, electrical performance tests, and safety tests such as heating and acupuncture. The test results are shown in Table 1.

[0100] By comparing the results of Examples 1-4 with those of Comparative Example 1, it can be seen that, compared with conventional semi-solid technology without solid electrolyte film, the preparation method of a semi-solid lithium-ion battery of the present invention provides the battery with excellent cycle performance, rate performance, low-temperature discharge and other electrical properties and safety performance such as acupuncture through the positive electrode-supported solid electrolyte film frame prepared by a double-layer coating process. In addition, the battery capacity is also improved to a certain extent.

[0101] Table 1

[0102]

[0103] The present invention discloses a semi-solid lithium-ion battery and a method for preparing the same. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The products of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the products described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

Claims

1. A semi-solid lithium-ion battery, characterized in that: include: Positive electrode sheet, negative electrode sheet, separator and electrolyte; The separator separates the positive electrode sheet from the negative electrode sheet, and the negative electrode is wrapped around the positive electrode and stacked to form a battery cell. The battery cell is packaged into a battery shell and injected with electrolyte. After precharging, degassing, and capacity separation processes, a semi-solid lithium-ion battery is obtained.

2. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: The following steps are involved: (1) mixing and homogenizing the active material, the conductive agent, the binder and the dispersant to obtain a first slurry; (2) mixing and homogenizing the solid electrolyte, the binder, the ionic liquid and the nanofiller to obtain a second slurry; (3) coating the first slurry on the current collector through a double-layer coating process, coating the second slurry on the first slurry, and obtaining a positive electrode sheet through rolling, slitting, and die-cutting processes; (4) mixing and homogenizing graphite, silicon-based negative electrode, conductive agent and binder to obtain negative electrode slurry, and obtaining negative electrode sheet through coating, rolling, striping and die cutting processes; (5) Assembling the positive electrode sheet, the negative electrode sheet and the separator into a core package by laminating, and obtaining a dry battery cell by welding, putting aluminum plastic film into the shell, and heat sealing; (6) The electrolyte is injected into the dry battery cell, and a semi-solid lithium-ion battery is obtained after pre-charging, degassing, and capacity separation processes.

3. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: In step (1), the active material is selected from one or more of ternary material LiNi x Co y M 1-x-y O2, lithium iron phosphate, lithium manganese iron phosphate, wherein in the ternary material LiNi x Co y M 1-x-y O2, M is at least one of Mn and Al, 0.4 ≤ x < 1, 0 < y < 0.2; the conductive agent is selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and Super-P; the binder is selected from one or two of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; the dispersant is selected from one or two of tripropyl phosphate, dibutyl phosphate, and polyether-modified polysiloxane copolymer.

4. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: In step (1), the mass ratio of the active material, the conductive agent, the binder and the dispersant is (95-99.25): (0.2-5): (0.5-2): (0.05-0.5).

5. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: In step (2), the solid electrolyte is selected from one or more of lithium lanthanum zirconium titanate, lithium aluminum titanium phosphate, and lithium zirconium silicon phosphorus; the binder is selected from one or two of polyvinylidene fluoride and polyvinylidene fluoride-hexafluoropropylene; the ionic liquid is selected from 1-ethyl-3-methylimidazoline bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazole dicyanamide, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-ethyl-3-methylimidazole dicyanomethylene, 1-butyl-3-methylimidazole dicyanamide, and 1-butyl-3-methylimidazole dicyanamide; the nanofiller is selected from one or more of titanium dioxide, silicon dioxide, graphene, and Maxim.

6. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: In step (2), the mass ratio of the solid electrolyte, binder, ionic liquid and nanofiller is (20-99): (0.5-60): (0.4-20): (0-5).

7. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: In step (4), the silicon-based negative electrode is selected from one or more of silicon oxide, silicon carbon, and silicon nanowires; the conductive agent is selected from one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphene, and Super-P; and the binder is selected from one or more of polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose, and styrene-butadiene rubber.

8. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: In step (4), the mass ratio of the graphite, the silicon-based negative electrode, the conductive agent and the binder is (1-96): (1-96): (0.1-5): (1-5).

9. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: In step (5), the diaphragm is selected from a ceramic single-sided / double-sided coated diaphragm, a solid electrolyte single-sided / double-sided coated diaphragm, and a single-sided / double-sided glue-coated diaphragm.

10. The method for preparing a semi-solid lithium-ion battery according to claim 1, characterized in that: In step (3), the coating thickness of the second slurry is 2-20 μm; in step (6), the electrolyte accounts for 2-15% of the total weight of the dry battery cell.

Citation Information

Cited By

  • Solid-state battery processing method

    CN119764597A